(−)-Hydroxycitric acid reduced fat deposition via regulating lipid metabolism-related gene expression in broiler chickens. Issue 1 (December 2016) - Han, Jing; Li, Longlong; Wang, Dian; Ma, Haitian
Abstract Background Chicken as a delicious food for a long history, and it is well known that excess fat deposition in broiler chickens will not only induced metabolic diseases, but also lead to adverse effect in the consumer's health. (−)-Hydroxycitric acid (HCA), a major active ingredient ofGarcinia Cambogia extracts, had shown to suppress fat accumulation in animals and humans. While, the precise physiological mechanism of HCA has not yet been full clarified, especially its action in broiler chickens. Thus, this study aimed to assess the effect of (−)-HCA on lipid metabolism in broiler chickens. Methods A total of 120 1-day-old broiler chickens were randomly allocated to four groups, with each group was repeated three times with 10 birds. Birds received a commercial diet supplemented with (−)-HCA at 0, 1000, 2000 or 3000 mg/kg, respectively, for a period of 4 weeksad libitum . Results Body weight (BW) in the 2000 and 3000 mg/kg (−)-HCA groups was significantly decreased (P < 0.05) than that in control group. A significantly decreased of serum triglyceride (TG) and density lipoprotein-cholesterol (LDL-C) content were observed in 3000 mg/kg (−)-HCA group (P < 0.05). Broiler chickens supplmented with 2000 and 3000 mg/kg (−)-HCA had pronouncedly higher hepatic lipase (HL) activity, hepatic glycogen and non-esterified fatty acid (NEFA) contents in liver (P < 0.05). Serum free triiodothyronine (FT3) and thyroxin (T4) contents were significantly higher in 3000 mg/kg (−)-HCA group (P < 0.05) compared with the control group. Supplemental (−)-HCA markedly decreased fatty acid synthase (FAS) and sterol regulatory element binding protein-1c (SREBP-1c) (P < 0.05) mRNA levels, while the mRNA abundance of adenosine 5′-monophosphate-activated protein kinaseβ2 (AMPKβ2) (P < 0.05) was significantly increased. In addition, ATP-citrate lyase (ACLY) mRNA level (P < 0.05) was significantly decreased in broiler chickens supplemented with 3000 mg/kg (−)-HCA. No differences was observed on carnitine palmitoyl transferase-I(CPT-I), while peroxisome proliferators-activated receptor α (PPARα) mRNA level (P < 0.05) was significantly increased in broiler chickens supplemented with 2000 and 3000 mg/kg (−)-HCA. Conclusions Supplemental (−)-HCA inhibited lipogenesis by inhibiting ACLY, SREBP-1c and FAS expression, and accelerated lipolysis through enhancing HL activity and PPARα expression, which eventually led to the reduced abdominal fat deposition in broiler chickens. Graphical abstract Mechanism of (−)-HCA effect on hepatic lipids metabolism.